Durability and Moisture Dynamics of Douglas-Fir Wood From Slovenia - Humar, Miha; Vek, Viljem; Oven, Primož; Lesar, Boštjan; Kržišnik, Davor; Keržič, Eli; Hočevar, Miha; Brus, Robert (Frontiers in Plant Science, 2022)
Wood in outdoor applications is subject to various decomposition factors. Wood degradation can be prevented by construction details, biocide protection of wood, wood modification or selection of naturally durable species. Unfortunately, most species in Europe do not have naturally durable wood. Imported tree species represent a new pool from which we can draw wood species with better natural durability and better resilience towards climate change. The performance of wood when used outdoors depends on the biologically active compounds (extractives) and the water exclusion efficacy. Considering decay, presence of biologically active compounds and water exclusion efficacy, we can estimate the density, modulus of elasticity, extractive content and resistance dose, which reflects the material properties of wood. Recently, the most commonly used model for this purpose is Meyer-Veltrup. Literature data indicate that the durability of the wood from native and new sites is not always comparable, so it is necessary to determine the resistance of non-native wood species from new sites. This paper presents original data on the wood’s overall durability from American Douglas fir (Pseudotsuga menziesii) grown in Slovenia. Experimental data show that the mature heartwood of Douglas fir is more durable than the wood of European larch (Larix decidua). Durability can be attributed to good water exclusion efficacy and inherent durability. Inherent durability is primarily the result of the high content of extractives. Based on the results, it can be concluded that American Douglas fir grown in Central Europe has a high potential for outdoor use.